Pengaruh Kualitas Layanan Internal dan Kepuasan Kerja terhadap Kinerja Karyawan Hotel - Ni Luh Putu Surining Jati; I Ketut Surata; I Gusti Agung Febrianto (JURNAL BISNIS HOSPITALITI, 2021)
This research was conducted to analyze the influence of internal service quality on job performance, analyze the influence of job satisfaction on job performance, and analyze the influence of internal service quality and job satisfaction on job performance at The Ritz-Carlton Bali. Questionnaires as the data collection technique were distributed to employees at The Ritz-Carlton Bali as the respondents. The total samples were 85 respondents which identified using simple random sampling technique and Slovin formula as sampling technique. The measurements of this research used a Likert scale. The methods of data analysis used were classic assumption testing, coefficient determination, hypothesis test, and testing by SPSS version 24. The results of data analysis indicated that internal service quality has a positive and significant effect on job performance at The Ritz-Carlton Bali as proven by the value of tcount (3,259) > ttabel (1,663). Job satisfaction has a positive and significant effect on job performance at The Ritz-Carlton Bali as proven by the value of tcount 2,742 > ttabel (1,663). and Internal service quality and job satisfaction simultaneously have a contributing is 5,21% through to the job performance. While the other remaining 4,79% is influenced by the other variable studied in this research.